Lettre de M. Rolland, ministre de l'intérieur, à l'Assemblée nationale imprimée par ordre de l'Assemblée nationale - Roland de la Platière, Jean-Marie 1734-1793 (Imprimerie nationale, 1792)
Concerns the massacres in the prisons.
Keywords: Roland de La Platière, Jean-Marie <1734-1793>; Geschichte; Politik; Massacres -- France -- Paris -- Early works to 1800; Prisoners -- France -- Early works to 1800; Prisons -- France -- Early works to 1800; Frankreich; France -- History -- Revolution, 1789-1799; France -- History -- Revolution, 1789-1799 -- Prisoners and prisons; France -- Politics and government -- 1789-1799